Evaluation of Brain Tumors Using Amide Proton Transfer Imaging: A Comparison of Normal Amide Proton Transfer Signal With Abnormal Amide Proton Transfer Signal Value. Issue 1 (1st September 2022) - Sugawara, Kazuaki; Miyati, Tosiaki; Wakabayashi, Hikaru; Yoshimaru, Daisuke; Komatsu, Shuhei; Hagiwara, Kazuchika; Saigusa, Kuniyasu; Ohno, Naoki
Abstract : Objective: The aim of the study was to evaluate the relationship of amide proton transfer (APT) signal characteristics in brain tumors and uninvolved brain tissue for patients with glioblastoma and those with brain metastases. Methods: Using the mDIXON 3D-APT sequence of the fast spin echo method, an APT image was obtained. The mean APT signal values of tumor core, peritumor edema, ipsilateral normal-appearing white matter (INAWM), and contralateral normal white matter (CNAWM) were obtained and compared between glioblastoma and brain metastases. Receiver operating characteristic curves were used to evaluate parameters for distinguishing between glioblastoma and brain metastases. In addition, the difference and change rate in APT signal values between tumor core and peritumoral edema (PE) and CNAWM were evaluated, respectively. Results: The APT signal values of glioblastoma were the highest in tumor core (3.41% ± 0.49%), followed by PE (2.24% ± 0.29%), INAWM (1.35% ± 0.15%), and CNAWM (1.26% ± 0.12%, P < 0.001). The APT signal value of brain metastases was the highest in tumor core (2.74% ± 0.34%), followed by PE (1.86% ± 0.35%), INAWM (1.17% ± 0.13%), and CNAWM (1.2% ± 0.09%, P < 0.01). The APT change rate (between PE and CNAWM) was not significantly different at 78% and 56% for glioblastoma and brain metastases, respectively ( P > 0.05). Conclusions: Performing APT imaging under the same parameters used in this study may aid in the identification of brain tumors.